Neurocognitive Development of Risk Aversion from Early Childhood to Adulthood - Paulsen, David; Carter, R. McKell; Platt, Michael; Huettel, Scott A.; Brannon, Elizabeth M. (Frontiers in Human Neuroscience, 2012)
Human adults tend to avoid risk. In behavioral economic studies, risk aversion is manifest as a preference for sure gains over uncertain gains. However, children tend to be less averse to risk than adults. Given that many of the brain regions supporting decision making under risk do not reach maturity until late adolescence or beyond it is possible that mature risk-averse behavior may emerge from the development of decision-making circuitry. To explore this hypothesis, we tested 6- to 8-year-old children, 14- to 16-year-old adolescents, and young adults in a risky-decision task during functional magnetic resonance imaging (fMRI) data acquisition. We found a number of decision-related brain regions to increase in activation with age during decision making, including areas associated with contextual memory retrieval and the incorporation of prior outcomes into the current decision-making strategy, e.g. insula, hippocampus and amygdala. Further, children who were more risk averse showed increased activation during decision making in vmPFC and ventral striatum. Our findings indicate that the emergence of adult levels of risk aversion co-occurs with the recruitment of regions supporting decision making under risk, including the integration of prior outcomes into current decision-making behavior. This pattern of results suggests that individual differences in the development of risk aversion may reflect differences in the maturation of these neural processes.